Establishment of a Community-Based Halal Certification Body: A Case Study of Halal International Trust Organization (HITO) in Japan - Gandhi, Prima; Hidayat, Muhammad Muharram; Hapsari, Kharisma Fitri (Halal Studies and Society, 2025)
Japan’s aging society, driven by declining birth rates, urbanization, and sociocultural factors, has necessitated increased labor migration from countries such as Indonesia, which now accounts for over 149,000 residents (2023) and 430,000 annual tourists (2023). This demographic shift has amplified the demand for halal products among Indonesia’s Muslim majority, yet Japan lacks formal halal regulations, relying instead on third-party certifications such as the Japan Halal Association (est. 2010). To address this gap, the Indonesian Embassy (KBRI) in Tokyo and Keluarga Masyarakat Islam Indonesia or Indonesian Muslims Association (KMII) Japan initiated the establishment of a community-based halal certification institution for Indonesian Muslims in Japan to address this gap. This study aimed to determine the establishment of the Halal International Trust Organization (HITO) in Japan. The methodology of this study was descriptive qualitative. The data collection process was conducted through interviews to obtain data and observations. This study was conducted in Tokyo. The informants were selected using purposive sampling techniques. The informants involved in the study were the management of KMII, HITO, and officials at KBRI Tokyo. HITO operates under KMII Japan Ippan Shadan Hojin (a legally recognized non-profit). HITO’s five functions include setting locally adapted halal standards, auditing products, training auditors, and fostering socioeconomic integration. Its organizational structure features a supervisory board, advisory council, and daily management team supported by 31 trained assistants across nine prefectures. The certification process involves online submissions, facilitator validation, approval of ‘fatwa’ council, and digital certificate issuance, prioritizing affordability for Small and Medium Enterprises (SMEs).